STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) TYPE COOPERATIVE LEARNING MODEL TO IMPROVE THE COOPERATION CAPABILITY OF CLASS IV PRIMARY STUDENTS - Fauziyyah, Listya Nur; Kuswendi, Uus; Nurfurqon, Faridillah Fahmi; Murni, Sukma (Journal Of Educational Experts (JEE), 2024)
This study examines the improvement of cooperative skills using a cooperative learning model of the student team achievement division (STAD) type and students' responses to learning using the STAD type cooperative model. The research method used is a mixed method with an explanatory sequential design. This research was conducted in one of the elementary schools in Batujajar with a total of 31 students. In this model, a group is given treatment and then given observation of results and processes. The data collection technique in this study uses observation sheets, student response questionnaires. The data analysis technique uses a normality test and an N-gain test assisted by the SPSS application. Based on the results of the study, the STAD type cooperative training model in improving cooperation ability has increased, as seen based on the results of the N-gain test with a score of 0.43 with the medium category, with a percentage of pretest scores of 63% and an increase of 17% in the posttest results, which is 80%. The learning model is said to be effective if the N-gain score obtained > 0.3 in the medium category, and students show a good response while using the STAD-type cooperative model based on the results of the questionnaire with an average score of 85, 9 in the very good category.